Bio-corrosion on Aluminium 6063 by Escherichia coli in Marine Environment - Herman Pratikno; Harmin Sulistiyaning Titah (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2017)
Biological corrosion is caused by presence of microbes in environment. Escherichia coli causes serious biofouling in various environments and its pronounced influence on marine biofouling that causing serious problems such as accelerated corrosion. E. coli shares similar properties with most marine bacteria and it was extensively studied for marine environment. The aims of this research was to determine the corrosion rate on Aluminium 6063 by E. coli in deep seawater (salinity of 33‰), medium seawater (salinity of 35‰), shallow seawater (salinity of 37‰). Based on results, bio-corrosion rate on Al 6063 were higher than control. The bio-corrosion rate Al 6063 at day 28 in salinity of 37‰ was 1.1233 mm/year, meanwhile the corrosion rate for control was 0.7225 mm/year. Visual observation showed that corrosion occured on surface on specimen. Macrostructure observation showed that white spots occured on surface of specimen with E. coli was higher than specimen in control (without E. coli, only saline water) It was indicating that presence of E. coli caused increasing of corrosion rate on Al 6063.